The Relationship Between Iron Deficiency and Asthma Severity: Detection The Role of Gender and Ferritin Level - Faisal, Samih (University of Thi-Qar Journal of Science, 2024)
Emerging research suggests a complex interplay between asthma severity and ferritin levels, with evidence indicating that lower serum ferritin may be associated with increased asthma exacerbations, highlighting the potential role of iron homeostasis in respiratory health and disease management. The study aims to examine the impact of ferritin levels on asthma severity, assess the moderating effect of gender, and identify biomarkers that exacerbate symptoms in the context of low ferritin. This study enrolled 180 individuals over 18 years, including 120 allergic asthma patients and 60 healthy controls. Asthma patients were categorized based on ferritin levels into 43 males and 17 females with normal levels, and 17 males and 43 females with low levels. The study excluded individuals with other respiratory, autoimmune, or oncologic diseases, and smokers. Blood samples were collected for complete blood count (CBC), ferritin, and Immunoglobulin E (IgE) measurements, with serum samples frozen at -70°C for further analysis. Out of 180 participants, 120 (66.6%) were asthma cases, split evenly between normal and low ferritin levels. The study found significant hematocrit differences (P < 0.01), with the lowest levels in the low ferritin asthma group (35.18 ± 6.74). Ferritin and IgE levels varied markedly across groups (P < 0.05 and P < 0.001, respectively), with the lowest ferritin (9.80 ± 2.39 ng/ml) and highest IgE (327.91 ± 106.81 IU/ml) in the low ferritin asthma group. Regression analysis showed an inverse relationship between ferritin levels and asthma severity (B = -20.46, P < 0.001),